Education Leaders’ Health in the Integral Perspective. A Research Account - Blajet, Piotr; Przybborowska, Beata; Baczała, Ditta; Binnebesel, Józef (Wydawnictwo Naukowe UAM, 2018)
The article aims at presenting the integral approach to the health of Polish education leaders’ (head teachers) in light of Ken Wilber’s map (four classes of factors responsible for health), in the social-ecological model of health. Material and Methods: The Matrix of ReflectivenessDevelopment, an original self-observation schedule, was applied as a research tool. 46 head teachers were examined. Results: The results show that the respondents look after their own health the least. Relaxation is something they associate with mental health, while physical health is not high on their list of priorities. Conclusions: The respondents mainly focus on professional and family lives. Very little focus is placed on reflectionand an integral approach to health. The analysis of research results highlights the challenges that education at each level, including health education, must face.
Zdrowie liderów oświaty w perspektywie integralnej. Raport z badań
Keywords: health; education leader; integral model of health; education; health education